Separation Axioms on Topological Space - A Unified Version (European Journal of Pure and Applied Mathematics, 2013)
In this paper a new kind of sets called generalized closed sets are introduced and studied in a topological space by using the concept of operation in a topological space.Â  Some of their properties are investigated. Finally, some characterizations of $ψ_g$-regular, $ψ_g$-normal spaces are given.